H3e/H4e Ratio in Olivines from Linosa, Ustica, and Pantelleria Islands (Southern Italy). (1st March 2012) - Fourré, Elise; Allard, Patrick; Jean-Baptiste, Philippe; Cellura, Dario; Parello, Francesco
Abstract : We report helium isotope data for 0.03–1 Ma olivine-bearing basaltic hawaiites from three volcanoes of the southern Italy magmatic province (Ustica, Pantelleria, and Linosa Islands). HomogenousH 3 e /H 4 e ratios (range: 7.3–7.6 R a ) for the three islands, and their similarity with the ratio of modern volcanic gases on Pantelleria, indicate a common magmatic end-member. In particular, Ustica (7.6 ± 0.2 R a ) clearly differs from the nearby Aeolian Islands Arc volcanism, despite its location on the Tyrrhenian side of the plate boundary. Although limited in size, our data set complements the large existing database for helium isotope in southern Italy and adds further constraints upon the spatial extent of intraplate alkaline volcanism in southern Mediterranea. As already discussed by others, the He-Pb isotopic signature of this magmatic province indicates a derivation from a mantle diapir of a OIB-type that is partially diluted by the depleted upper mantle (MORB mantle) at its periphery.